Application of the Fitradeoff Method to the problem of classification for customers in the polyurethane sector: a case study - Mata, Henry Ronaldo Lopez; Vieira, Jose Geraldo Vidal (Brazilian Journal of Production Engineering, 2026)
In a context of globalization of raw materials (polyol and isocyanate) in the polyurethane sector, within the Business-to-Business model, Customer Relationship Management is essential in decision-making to determine buyer segmentation based on three levels of prioritization. This research uses the compensatory Multi-Criteria Decision Analysis method, FITradeoff, to classify the ten raw material buyers of a chemical company using four qualitative and quantitative criteria. The robustness of the model was ensured by the sensitivity analysis performed by the software on the variations in the performance of the criteria. The data were subtracted from the company’s database for the period 2024. In the results obtained, three buyers were classified as high impact, three as medium impact, and four as low impact, providing the company with strategic decisions on product planning and marketing and sales actions in a more efficient manner.